GH/IGF-I and bone resorption in vivo and in vitro - Ueland, Thor (European journal of endocrinology, 2005)
IGF-I may act as one of several coupling agents by activating bone formation and bone resorption. In vivo studies in normal subjects, postmenopausal women and patients with excess or diminished GH production (acromegaly and GHD) indicate that both GH and IGF-I activate osteoclasts, but that GH has a more pronounced effect, independently of IGF-I. In vitro, GH and IGF receptors have been demonstrated on osteoclasts and both GH and IGF-I may directly modify osteoclast function and activity. In addition to direct effects on osteoclasts, GH and IGF-I may affect bone resorption indirectly by stimulating release of paracrine mediators that regulate osteoclastic resorption (cytokines). Critical for the bone resorptive process is the balance between OPG and RANKL, which is regulated by many systemic factors. In vivo and in vitro, GH/IGF-I may modulate this balance but these studies are difficult to interpret, reflecting the complexity of this system. Increased OPG expression may possibly protect against GH/IGF-I-induced bone resorption and potentially be important for the long-term beneficial effects of GH replacement. Further studies investigating the OPG/RANKL ratio and system in experimental and transgenic GH/IGF models may clarify these issues.